Assessing Digital Literacy Skills among Indonesian University Students in the Age of Society 5.0 - Islamia, Intan; Rahman Arif, Andry (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Students, as the younger generation, must have adequate digital literacy skills to adapt and develop in this era. This research aims to identify and analyze portraits of students' digital literacy skills in Indonesia in the 5.0 era. This research used quantitative methods involving 99 student respondents from various campuses throughout Indonesia. The instrument used in this research is a questionnaire developed by Nugroho (2020), which uses the digital literacy measurement component from Digital Digital Literacy Across the Curriculum (Hague & Payton, 2010) with a reliability score of α = 0.961. The research results showed that most (73%) respondents were in the medium digital literacy skills category. The results also show that stu3edents achieved high scores in the skills components of seeking and selecting information, communication, digital security, collaboration, and creativity. Mid-average scores were achieved for the functional skills component, critical thinking, and evaluation abilities. Meanwhile, the lowest score was in the social and cultural understanding component. The findings of this research can be used for various purposes, such as designing digital literacy education and training programs that are right on target, developing digital tools and platforms that are easy to use by people with various levels of digital literacy, and creating effective policies and regulations related to digital literacy.